Elastic anisotropy of the wellington shale at seismic frequencies - laboratory measurements - Mikhaltsevitch, Vassili; Lebedev, M.; Pervukhina, M.; Zandi, S.; Gurevich, B. (2016)
The rapid development of shale oil and gas production due to advances in directional well drilling and hydraulic fracturing has raised increasing industrial need for characterizing and understanding the elastic properties of shales. The elastic anisotropy of shales is becoming an important factor in seismic data interpretation and reservoir characterization. The anisotropic behavior of shales is usually associated with the properties of a transversely isotropic medium, which are determined by five elastic constants such as five independent components of the compliance or stiffness matrix. In this study we applied the laboratory low-frequency technique based on stress-strain relationship to measure five independent compliance components and estimate Thomsen's anisotropy parameters. We investigated three shale samples from the Wellington formation cored along the horizontal, vertical and 45°-inclination directions with respect to the bedding plane at seismic frequencies between 0.1 Hz and 100 Hz. The laboratory tests were carried out at a relatively low confining pressure to avoid a laceration of strain gauges due to the high compressibility of Wellington shale. Our measurements demonstrate that the low-frequency measurements can be successfully used for characterization of the elastic anisotropy of shales.